Impact of Microfinance on Rural Households in the Philippines - Aniceto C. Orbeta; Clarence G. Dingcong; Toshio Kondo; Christine Infantado (Philippine Institute for Development Studies (PIDS), 2008)
This paper reports on the impact evaluation study of the Rural Microenterprise Finance Project (RMFP) in the Philippines. RMFP aimed to support efforts of the Government of the Philippines to strengthen rural financial institutions by assisting organizations that employed the Grameen Bank Approach (GBA) in providing credit to the poor. The project was implemented by the Peoples Credit and Finance Corporation (PCFC) and funded by the Asian Development Bank. The evaluation uses a quasi-experimental design with incoming clients of randomly selected participating microfinance institutions as the comparison group. An important innovation in the study is the inclusion of the appropriate number of former clients among the treatment group. Qualified nonparticipating households provide the control for area effects. The impact estimation uses the difference-in-difference estimation technique which effectively controls for the known sources of biases namely: nonrandom program participation (sample selection), nonrandom program placement, and nonrandom drop-out. The results led the authors to recommend that for microfinance programs to be effective as a poverty-alleviation tool there is a need to review and constantly monitor the effectiveness of the targeting procedures. In addition, it was pointed out that there may be a need to assist the poor in selecting appropriate projects that not only ensure loan repayment but also generate ample profit as well.
Keywords: 330; microfinance; Philippines; impact evaluation; quasi-experimental design; Mikrofinanzierung; Privater Haushalt; Entwicklungspolitik; Ländlicher Raum; Wirkungsanalyse; Test; Schätzung; Philippinen